PERANCANGAN MEDIA PEMBELAJARAN BAHASA INGGRIS MENGGUNAKAN MIT APP INVENTOR DI SMPN 4 BUKITTINGGI - Muhammad Wido Hadi Kusuma; Gusnita Darmawati; Firdaus Annas; Yulifda Elin Yuspita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to design an Android-based English learning media using MIT App Inventor at SMPN 4 Bukittinggi. The background of this study is low student learning interest, the use of conventional learning media, and the lack of technology utilization in the teaching and learning process. The purpose of this study is to design valid, practical, and effective English learning media using the MIT App Inventor application at SMPN 4 Bukittinggi. This study used the Research and Development (R&D) method using the Hannafin and Peck model, which consists of three stages: needs analysis (Needs Assessment), design (Design), development, and implementation (Develop/Implement). Product testing used in the study consisted of validity, effectiveness, and practicality. The results showed that the designed learning media can help improve student motivation and understanding of English material. The validity test obtained an average score of 0.92 (valid), the practicality test obtained an average score of 0.88 (very practical), and the effectiveness test showed an average score of 0.81 (effective). This media is expected to be an innovative learning solution and support teachers in delivering material in an interactive and engaging manner.